Optimal and stable supply chain services system: integrating management services with robust optimisation modelling. (29th December 2014) - Lou, Catherine Xiaocui; Dai, Wei
Developments in supply chain management (SCM) have dramatically increased within the past few years to cover a wide range of cross–disciplinary topics. With the significant developments in both technologies and business environments, a service system is proposed to work optimally under complex, globalised supply chain environments. Following the studies on SCM theories, this research develops a robust enterprise supply chain services framework taking into account of risk management in firm governance. Consequently, a robust supply chain services system (RSCSS) was built by combining optimisation modelling with the six–core management service modules of knowledge, data, task, information, communication and risk. In this system, the robust optimisation method was used to manage uncertainties. Importantly, by integrating the six–core management services modules with robust optimisation, this RSCSS can assist in supporting optimal and stable operations in a wide range of enterprises, especially for small and medium enterprises running global businesses dynamically and economically.